2010
DOI: 10.1124/jpet.110.176362
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Glucagon-Like Peptide-1 Receptor Signaling by Naturally Occurring and Synthetic Flavonoids

Abstract: The glucagon-like peptide 1 receptor (GLP-1R) is a promising target for the treatment of type II diabetes mellitus because of its role in metabolic homeostasis. In recent years, difficulties with peptide therapies have driven the search for small-molecule compounds to modulate the activity of this receptor. We recently identified quercetin, a naturally occurring flavonoid, as a probe-dependent, pathway-selective allosteric modulator of GLP-1R-mediated signaling. Using Chinese hamster ovary cells expressing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 28 publications
(36 reference statements)
1
56
0
Order By: Relevance
“…Whereas discovery of surrogate agonists that use a receptor binding and activation mechanism similar to GLP-1 is probably difficult, we have reported that small molecules acting allosterically may be a more feasible approach (Koole et al, 2010;Wootten et al, 2011). The data presented here explore the hypothesis that a GLP-1 receptor allosteric modulator can potentiate the activity of the endogenous hormone oxyntomodulin on the GLP-1 receptor and thereby offer an additional small molecule approach to enhance GLP-1 receptor signaling.…”
Section: Allosteric Modulation Of Oxyntomodulin At the Glp-1 Receptormentioning
confidence: 80%
“…Whereas discovery of surrogate agonists that use a receptor binding and activation mechanism similar to GLP-1 is probably difficult, we have reported that small molecules acting allosterically may be a more feasible approach (Koole et al, 2010;Wootten et al, 2011). The data presented here explore the hypothesis that a GLP-1 receptor allosteric modulator can potentiate the activity of the endogenous hormone oxyntomodulin on the GLP-1 receptor and thereby offer an additional small molecule approach to enhance GLP-1 receptor signaling.…”
Section: Allosteric Modulation Of Oxyntomodulin At the Glp-1 Receptormentioning
confidence: 80%
“…Class B peptide hormone GPCRs have been particularly difficult to target therapeutically because of the diffuse pharmacophore associated with the peptide orthosteric site, which is extracellular and involves multiple points of interaction with the N terminus and top of the transmembrane bundle. However, a number of small molecules have recently emerged that act allosterically, examples of which are found with molecules targeting the corticotrophin releasing factor-1 receptor (Hoare et al, 2008), the calcitonin receptor (Dong et al, 2009), and the glucagon-like peptide-1 receptor (Knudsen et al, 2007;Wootten et al, 2011). These findings suggest that the allosteric approach represents a viable path forward for discovering small molecules directed against these peptide-hormone receptors.…”
Section: B G Protein-coupled Receptorsmentioning
confidence: 94%
“…The same trend was also evident for 4Ј-hydroxyflavonol and 3Ј4Ј-dihydroxyflavonol, suggesting hydroxyl groups in these positions are an important chemical feature engendering cooperativity. Conversely, the flavanoid catechin negatively modulated GLP-1(7-36)NH 2 , GLP-1(7-37), GLP-1(1-36)NH 2 , and to a lesser extent exendin-4 and GLP-1 (1-37), but not oxyntomodulin in cAMP accumulation assays (59). In both cases, the absence of modulation in agonist binding affinity suggests an efficacy-driven mechanism of action.…”
Section: Allosteric Ligands Alter the Signal Bias Of Peptidic Ligandsmentioning
confidence: 96%
“…In both cases, the absence of modulation in agonist binding affinity suggests an efficacy-driven mechanism of action. Furthermore, the differential cooperativity in binding and signaling assays for quercetin, 4Ј-hydroxyflavonol, 3Ј4Ј-dihydroxyflavonol, and catechin, and indeed also compound 2 and BETP (59), are clear examples that the action of allosteric modulators cannot be classified solely through measurement of one pathway. This has also been exemplified at other receptors, including the cannabinoid CB 1 receptor, whereby allosteric Organon Research compounds positively modulate agonist binding affinity but negatively modulate agonist-mediated luciferase signaling (60).…”
Section: Allosteric Ligands Alter the Signal Bias Of Peptidic Ligandsmentioning
confidence: 98%